Processes for creating an interprofessional mental health identity among pre-registration healthcare students: A scoping review protocol - Melissa Owens; Gérard Charl Filies; Molly Crosland; Claire Carswell (PLoS ONE, 2025)
Background Developing an interprofessional mental health identity among pre-registration (licensure) healthcare students is critical for promoting effective interprofessional collaboration in mental health care. An interprofessional mental health identity refers to the shared beliefs, values and attitudes that will enable healthcare students/professionals to work together effectively in addressing mental health issues and foster interprofessional collaborative person-centred practice. However, the processes and strategies for facilitating this amongst pre-registration healthcare students are not clearly defined or understood. This scoping review aims to map the available literature on how interprofessional mental health identity is created for pre-registration healthcare students. Methods We will follow the five stages of Arksey and O’Malley’s Framework and identify our search terms using the ‘population’, ‘concept’ and ‘context’ (PCC) criteria. We will search CINAHL, Medline, British Nursing Database, PsycInfo, Cochrane Library and AMED from 1990 to May 2024. Retrieved records will be managed in Covidence and screened independently by two reviewers. Data extraction forms will be developed to capture relevant data related to the review aim. The forms will be piloted, and two independent reviewers will complete the data extraction process. Narrative synthesis will be used to provide a descriptive overview of the included articles. Discussion Little is known about the process by which pre-registration healthcare students develop an interprofessional mental health identity. Therefore, this scoping review will draw together existing research to create a conceptual model for the process of developing an interprofessional mental health identity.